Productive and reproductive performance of heifers fed different levels of urea in the diet - Silva, Alessandra [UNESP]; Neiva, José Neuman Miranda; Araujo, Vera Lucia; Falcão, Alencariano Jose Silva; Borges, Álan Maia (Universidade Federal do Ceará, 2010)
The objective of the present study was to evaluate the nutrient intake, blood parameters, follicular diameter and performance of pre-puberty crossbred heifers fed isoproteic diets (14.1%CP) containing 0.0; 0.44; 0.88 and 1.32% urea on the total dry matter (DM) of the diet, with a 77:23 roughage:concentrate ratio. Twenty-four 18- month old heifers (Holstein x Zebu), 277.9 kg mean live weight (LW) were used, distributed in four treatments and six replications in a randomized complete design. The following were evaluated: dry matter intake (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), ether extract (EE), hemicellulose (HEM), plasmatic ureic nitrogen (PUN), plasmatic glucose, plasmatic total cholesterol, follicular diameter and daily weight gain (DWG). No influence of the urea levels in the diet was observed on NDF and HEM intake. A maximum intake was obtained of DM (8.75 kg day-1), CP (0.88 kg day-1), ADF (2.5 kg day-1) and EE (0.17 kg day-1) respectively for the levels 0.7, 0.8, 0.7 and 0.7% urea in total DM. The 0.6%; 0.77% and 0.6% urea levels in diet were the critical points for obtaining maximum response for the PUN (10.96 mg dL-1) and plasmatic glucose(84.97 mg dL-1) concentrations and, for follicular diameter (11.08 mm) on the 40th; 24th and 31st day, respectively. The plasmatic total cholesterol concentration and DWG were not influenced by the urea added to the diet, with averages of 119.39 mg dL-1 and 1.66 kg day-1, respectively. It was concluded that urea can be added up to 1.32% on the total DM of the diet for pre-puberty crossbred heifers.

Com o presente trabalho objetivou-se avaliar o consumo de nutrientes, parâmetros sangüíneos, diâmetro folicular e desempenho de novilhas mestiças pré-púberes alimentadas com dietas isoprotéicas (14,1%PB) contendo 0,0; 0,44; 0,88 e 1,32% de uréia na matéria seca (MS) total, com relação volumoso:concentrado 77:23. Utilizaram-se vinte e quatro novilhas (Holandês x Zebu) com média de 277,9 kg de peso vivo (PV) e 18 meses de idade, distribuídas em quatro tratamentos e seis repetições em delineamento inteiramente casualizado. Foram avaliados consumos de matéria seca (MS), proteína bruta (PB), fibra em detergente neutro (FDN), fibra em detergente ácido (FDA), extrato etéreo (EE), hemicelulose (HEM), nitrogênio uréico plasmático (NUP), glicose plasmática, colesterol plasmático total, máximo diâmetro folicular e ganho de peso diário (GPD). Não foi observada influencia dos níveis de uréia na dieta sobre os consumos de FDN e HEM. Obteve-se o máximo consumo de MS (8,75 kg dia-1), PB (0,88 kg dia-1), FDA (2,5 kg dia-1) e EE (0,17 kg dia-1) respectivamente para os níveis 0,7; 0,8; 0,7 e 0,7% de uréia na MS total da dieta. Os níveis 0,6%; 0,77% e 0,6% de uréia na dieta foram os pontos críticos para obtenção de resposta máxima para as concentrações de NUP (10,96 mg dL-1) e glicose plasmática (84,97 mg dL-1) e, para o diâmetro folicular (11,08 mm) nos respectivos dias 40º; 24º e 31º. A concentração do colesterol plasmático total e o GPD não foram influenciados pela adição de uréia, com médias de 119,39 mg dL-1 e 1,66 kg dia-1, respectivamente. Conclui-se que a uréia pode ser adicionada até 1,32% na MS total da dieta para novilhas mestiças pré-púberes confinadas.
Desempenho produtivo e reprodutivo de novilhas alimentadas com diferentes níveis de uréia na Dieta
Keywords: Cholesterol; Feedlot; Plasmatic ureic nitrogen; Weight gain; Colesterol; Confinamento; Ganho de peso; Nitrogênio ureico plasmático